Natural Immunity of Sheep and Lambs Against the Schmallenberg Virus Infection. Issue 2 (6th August 2014) - Rodríguez‐Prieto, V.; Kukielka, D.; Mouriño, M.; Paradell, H.; Plaja, L.; Urniza, A.; Sánchez‐Vizcaíno, J. Manuel
Summary: Since the first reports of the Schmallenberg disease (SBD) outbreaks in late 2011, the disease has spread across Europe, affecting cattle and sheep farms. While Schmallenberg virus (SBV) causes a mild clinical disease in adults, infection of pregnant females may lead to the production of typical congenital malformations (CMFs) in their offspring. It is speculated that the immunity acquired after a SBV infection is effective in preventing further infections. However, this has not been proven in naturally infected sheep, especially if they are pregnant when reinfected. The aim of this study was to monitor the natural immunity in SBV‐infected sheep. Twenty‐four ewes from the only Spanish farm with a SBV OIE‐notified outbreak were sampled. Subsequently, nine pregnant ewes were inoculated with SBV infectious plasma under controlled conditions. Six of them were euthanized before delivery, and their fetuses were inspected for lesions indicative for the SBV infection. The three remaining ewes were allowed to deliver one lamb each. Inoculation of the lambs was scheduled at approx. 3 months after birth. All samples were analyzed for viral RNA by RT‐PCR, and for antibodies by an indirect ELISA and a virus neutralization test (VNT). The majority of the 24 ewes showed a serological reaction against SBV. The three ewes that were allowed to lamb down demonstrated variable degrees of seroconversion which corresponded to the levels of immune reaction observed in their lambs. Moreover, no viral RNA was detected, no lesions were observed in the fetuses, and no clinical signs were detected in the inoculated animals. These findings suggest that the immunity acquired by sheep following a natural SBV infection could be sufficient to stop SBV reinfection. However, vaccination could be a valuable tool to control SBV infections and associated economic losses as it affords a more uniform and predictable protection at the flock/herd level.